Stability of the austenitic phase, the hardness variation of manganese steels affected by heat and subjected to impacts - Heredia, Juan Carlos (2012)
In the present investigation the influence of heat is evaluated in the stability of the austenite phase of type Hadfield manganese steel with 12% manganese. The metallographic analysis and hardness testing takes place in specimens of ASTM A128 Grade Cast Steel E-1, in a state of hardening (austenitizing), and with different heating temperatures from 100 ° C, 200 ° C, 300 ° C, 400 ° C and 500 ° C. The results allow us to check and set the maximum temperatures in the austenitic matrix is stable and maintains its excellent mechanical properties.